Zircon U–Pb Ages and Geochemistry of Granite Porphyries in the Yangla Cu Deposit, SW China: Constraints on Petrogenesis and Tectonic Evolution of the Jinshajiang Suture Belt. (1st September 2020) - Li, Bo; Wang, Xinfu; Du, Lijuan; Xiang, Zuopeng; Tang, Guo; Huang, Zhilong
Abstract : Located in the eastern part of the Tethyan tectonic domain, the Jinshajiang Suture Belt (JSB), northwestern Yunnan, China, is notable for its large-scale distribution of Jurassic to Triassic granitoids that are genetically related to the evolution of the Paleo-Tethys Ocean and polymetallic mineralization. In this study, geochronological and geochemical analyses were conducted on three samples of these granite porphyries (GPs) using laser ablation inductively coupled plasma mass spectrometry and zircon U–Pb aging to reveal ages of 213 ± 15, 198.4 ± 8.6, and 195.3 ± 6.4 M a, respectively. These ages are younger than the emplacement ages of the granodiorites, at 208–239 Ma, suggesting that magmatic activities in the Yangla mining district likely continued for 44 Ma. These GPs are rich in large-ion lithophile elements such as Rb, Ba, Th, U, K, and La but are deficient in high field strength elements such as Ta, Nb, Ce, Zr, Hf, and Ti. Significant Pb enrichment and P depletion were noted, as were varying degrees of metallogenic element enrichment in the order of Cu > Pb > Zn . The total content of rare earth elements ( Σ REEs) of the GPs is in the range of 50.41–127.27 ppm and the LREE/HREE ratio is in the rage of 4.46–10.54. The GPs are rich in LREEs, with a high degree of differentiation noted between the LREEs and HREEs. The δ Eu (EuN /Eu∗ ) and δ Ce (CeN /Ce∗ ) values, at 0.53–0.86 and 0.79–0.98, indicate weak and slightly weak negative anomalies, respectively. The geochemical characteristics of the GPs indicate that these bodies are slightly metaluminous to peraluminous S-type granites in a calc–alkaline series that formed in a late-collisional or postcollisional tectonic setting. Three-component mixing of magmas including those of upper crust, lower crust, and mantle materials in addition to subsequent partial melting could have been responsible for the generation of these GPs in an epithermal low-pressure setting at <5 kbar.